Ectopic miRNA network and the crosstalk between different signalling pathways during EMT and MET - Razak, Eliza; Yusof, Faridah; Ahmad Raus, Raha (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The tumor microenvironment (TEM) comprise of various cellular and molecular components such as fibroblasts, immune cells, bone marrow-derived inflammatory cells, endothelial cells, extracellular matrix (ECM), and signaling molecules. The complex crosstalk between (TEM) components and malignant cells can give rise to tumorigenesis, progression, and angiogenesis as well as micro-metastasis and macro-metastasis. MicroRNAs (miRNAs) are small, non-coding extracellular RNAs involved in post-transcriptional regulation of gene silencing or degradation by base paring at open reading frame (ORF) region of the target mRNA. Recent advances in the miRNA field have driven to the understanding of multiple regulatory aspects concerning cancer biology. Aberrant miRNA expression in malignant tumors compared with normal tissue are promising biomarkers for cancer diagnosis. Epithelial-to-mesenchymal transition (EMT) is a reversible process in which neoplastic epithelial cells expressed mesenchymal phenotypes and resulting in alteration of cell autonomous mechanisms. EMT enables epithelial cells to lose their cell polarity, acquire cancer stem cell-like properties which favor tumor invasion, extravasation and metastasis. Mesenchymal–epithelial transition (MET) is the inverse process of EMT. This results in stabilization of distant metastases by permitting cancerous cells to recoup epithelial phenotypes and integrate into distant organs. Ectopic microRNA expression and disturbed signaling pathways have been associated with EMT and MET processes. This review describes the co-regulatory loops among miRNAs, target genes and important regulatory pathways involved in cancer.